Inovasi Program Edukasi Kreatif dalam Meningkatkan Literasi dan Numerasi Siswa Sekolah Dasar - Nur Sakinah Aries; Muhammad Faisal Lutfi Amri; Fidyawati Monoarfa; Reska Putri Ismail; Nurainun Nurainun (Journal on Education, 2025)
This study aims to describe the improvement of literacy and numeracy skills in fifth-grade students at SDN 3 Talaga Jaya through the Kampus Mengajar Angkatan VI program. The research subjects consisted of 29 students. A qualitative descriptive approach was used, with data collected through observations, interviews, tests, and document collection. The researcher acted as the main instrument in data collection and analysis. This study also presents quantitative data from the Pretest and Post Test results for both literacy and numeracy. The literacy program, which included storytelling activities and digital-based learning, was found to be effective in enhancing students' reading and text comprehension skills. The results showed significant improvements, with the percentage of students meeting the minimum literacy standard increasing from 24% in the Pretest to 78% in the Post Test, and numeracy rising from 18% to 72%. The teaching program, which involved drills, mathematical games, contextual problem visualization, and the integration of literacy, proved to be effective in improving students' literacy and numeracy skills. This study recommends the adoption of similar methods to enhance the quality of elementary education.